2018
DOI: 10.1097/qad.0000000000001828
|View full text |Cite
|
Sign up to set email alerts
|

Global population-level association between herpes simplex virus 2 prevalence and HIV prevalence

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…For FSW populations with HSV-2 prevalence ≥ 50%, HIV prevalence was higher and often exceeded 10%. Our findings based on analysis of empirical data substantiate mathematical modeling analyses predicting quantitatively such an association 8,9 , which also appears to exist for other populations 20 . The modeling analyses simulating HSV-2 and HIV propagation along diverse sexual networks demonstrated that HSV-2 prevalence ≥ 50% is indicative of substantial sexual risk behavior, sufficient to sustain large HIV epidemics in a sexual network 9 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…For FSW populations with HSV-2 prevalence ≥ 50%, HIV prevalence was higher and often exceeded 10%. Our findings based on analysis of empirical data substantiate mathematical modeling analyses predicting quantitatively such an association 8,9 , which also appears to exist for other populations 20 . The modeling analyses simulating HSV-2 and HIV propagation along diverse sexual networks demonstrated that HSV-2 prevalence ≥ 50% is indicative of substantial sexual risk behavior, sufficient to sustain large HIV epidemics in a sexual network 9 .…”
Section: Discussionsupporting
confidence: 83%
“…In total, 77 reports comprising 231 paired HSV-2 and HIV prevalence measures among FSWs, from 40 countries, were eligible for inclusion. These contributed to the database generated through our earlier systematic review 20 As the focus of this work is on examining the association between the two infections, it was pre-decided to restrict the analysis to settings where HIV has been introduced; we therefore excluded 37 paired measures with zero HIV prevalence from further analysis. After excluding measures with zero HIV prevalence, analysis was performed on a total of 194 paired measures from 33 countries ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This number was calculated based on a significance level of 5% and an HSV-1 seroprevalence for each age group of 88% with a 10% precision level, and an HSV-2 seroprevalence for each age group of 2% with a 4% precision level. We based the two seroprevalence figures used for the sample size calculations on previous studies conducted in different national populations living in Qatar (18,19), as well as global data (3,4,12,21). However, as there are limited to no data on HSV types 1 and 2 in Filipino and Indian populations, we set a higher precision level.…”
Section: Study Samplesmentioning
confidence: 99%
“…HSV-1 is generally acquired through the oral route during childhood with mild to serious morbidity, but evidence from the United States of America (USA) and Western Europe indicates a growing sexual acquisition through oral sex (5,9,10). HSV-2 is nearly always acquired sexually and is strongly associated with HIV infection (11)(12)(13), with its prevalence patterns providing key inferences about the structure of sexual networks (14). Evidence suggests also an association between HSV-1 and HSV-2 infections (15,16).…”
Section: Introductionmentioning
confidence: 99%